Medication Adherence Affects Risk of New Diabetes Complications: A Cohort Study. (September 2016) - Simpson, Scot H.; Lin, Mu; Eurich, Dean T.
Background: Previous outcomes-based studies of adherence to diabetes medications have focused on glycemic control and are limited by questions of temporality and uncontrolled confounding.Objective: This retrospective cohort study of new oral antidiabetic medication users examined the effect of adherence on risk of incident macrovascular and microvascular complications.Methods: A nationwide integrated insurance claims and laboratory database was used to identify new oral antidiabetic medication users between January 2004 and December 2009. People with preexisting complications were excluded and the remaining cohort was followed until development of a new diabetes complication or December 2010. Medication adherence was calculated at 3-month intervals and entered as a time-dependent variable in a Cox proportional hazards model. Covariables entered in the model included patient demographics, clinical laboratory data, a medical frailty indicator and a mortality risk score from the Johns Hopkins adjusted clinical groups system, and medication use at baseline.Results: Among the 54 505 included patients, the median age was 60 years, 28 125 (52%) were men, 1447 (3%) were considered frail, the mean mortality risk score was 33.7 (±11.1), and 9793 (18%) developed a new diabetes complication. Good adherence (medication possession ratio ≥0.8) was associated with a lower risk of a new microvascular or macrovascular diabetes complication (adjusted hazard ratio = 0.96; 95% CI = 0.92-1.00; P = 0.05).Conclusions: This study design addresses limitations of previous studies and found a small but significantly lower risk of new diabetes complications associated with good adherence to oral antidiabetic medications.